Developing Vocabulary Handbook for the Eighth Grade Students of Junior High School - Anggraeni, Salsabila; Syam, Andi Tenrisanna; Husnaini, Husnaini; Thayyib, Magfirah; Wahibah, Wahibah (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to develop a vocabulary handbook for eighth-grade students at SMP Negeri 8 Palopo. The researcher used Research and Development by adapting the ADDIE modelâ€”the participants of this study were eighth-grade students of SMP Negeri 8 Palopo and three expert validators. Data were collected through observation, interviews, students' questionnaires, and expert validation.Â The vocabulary handbook was developed by referring to the needs analysis and adapting a task-based language approach. The appropriate vocabulary handbook as a research product consists of: 1. three units of vocabulary handbook material, namely: What are you doing? My uncle is a zookeeper, and Bigger is sometimes better. 2. Variety of activities adapted from task-based 3. Attractive layout and media 4. Other skills like listening, reading, and writing are completed with exciting grammar and vocabulary. The suitability of the student vocabulary guidebook is evidenced by the results of student and teacher perceptions that were categorized into